Strategi Inovatif Odd One Out dalam Materi Pronunciation di Sekolah Dasar - Heru Prasetyo; Novita Sari (Edupro: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This Community Service (PKM) activity is motivated by the limited variety of English pronunciation learning strategies in elementary schools, which has an impact on low student involvement, lack of sound differentiation practice, and lack of confidence when practicing pronunciation. This PKM aims to improve teachers' competence in designing and implementing innovative "Odd One Out" strategies in pronunciation materials and strengthening students' learning experiences through phonological activities that are fun, structured, and according to the characteristics of children's development. The method of implementing PKM uses a participatory-qualitative approach through coordination stages with school partners, learning training and demonstrations, implementation assistance in the classroom, joint reflection, and observation-based monitoring and evaluation. Data was obtained through observation of the learning process, interviews with teachers and students, reflective discussions, and documentation of teaching tools and learning products. The results of the implementation showed an increase in teachers' readiness in choosing target sound materials, compiling "Odd One Out" activity sheets, and managing classes interactively. Students showed more active participation, courage to try pronunciation, and increased ability to distinguish sounds through the identification of words with different phonological patterns. This activity contributes to providing a practical and easily replicated pronunciation learning mentoring model, as well as implications for strengthening English learning in elementary schools that are more communicative, student-centered, and sustainable.